Development and psychometric assessment of the triage nurses' professional capability questionnaire in the emergency department - Mostafa Bijani; Mahnaz Rakhshan; Mohammad Fararouei; Camellia Torabizadeh (BMC, 2020)
Abstract Background Evaluation of triage nurses' professional capability is integral to identifying potentials for professional development and nurses' educational needs, thus, there is a need for valid instruments to assess their professional capability. The present study was conducted to develop and measure the reliability and validity of a triage nurses' professional capability questionnaire. Methods This exploratory research was conducted in two stages: in the first stage (the qualitative phase), the concept of professional capability in triage nurses was defined and the items of the questionnaire were developed through conventional content analysis. In the second stage (the quantitative phase), the psychometric properties of the questionnaire were assessed based on analyses of its face validity, content validity, construct validity, internal homogeneity, and consistency. Results The initial item pool consisted of 90 items, while the final scale was comprised of 35 items. The S-CVI/Ave of the questionnaire was found to be 0.96.The exploratory factor analysis showed that the factor loading of the items was between 0.46-0.89, all of which were significant, and the three dimensions introduced in the main instrument were verified with acceptable values. The overall intraclass correlation coefficient of the instrument was calculated to be 0.90. The reliability of the instrument was assessed in terms of its internal homogeneity where the Cronbach's alpha of the whole instrument was found to be 0.89. Conclusions The results showed that the questionnaire developed for assessment of triage nurses' professional capability is sufficiently reliable and valid and can be employed by nurse administrators to evaluate triage nurses' professional capability.